Transactions on Pattern Languages of Programming III - Noble, James; Johnson, Ralph; Zdun, Uwe.; Wallingford, Eugene; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
The Transactions on Pattern Languages of Programming subline aims to publish papers on patterns and pattern languages as applied to software design, development, and use, throughout all phases of the software life cycle, from requirements and design to implementation, maintenance and evolution. The primary focus of this LNCS Transactions subline is on patterns, pattern collections, and pattern languages themselves. The journal also includes reviews, survey articles, criticisms of patterns and pattern languages, as well as other research on patterns and pattern languages. This book, the third volume in the Transactions on Pattern Languages of Programming series, presents five papers that have been through a careful peer review process involving both pattern experts and domain experts. The papers present various pattern languages and a study of applying patterns and represent some of the best work that has been carried out in design patterns and pattern languages of programming over the last few years.
Keywords: Computer science; Software engineering; Information Systems; Computer Science; Software Engineering; Programming Languages, Compilers, Interpreters; Programming Techniques; Management of Computing and Information Systems